Endogenous and Exogenous Hormones and their Influence on the Response to Exercise-Induced Muscle Damage - Wageh, Mai (My University, 2025)
Exercise-induced muscle damage (EIMD) involves a complex cascade of structural, inflammatory, and myogenic responses that work together to repair and regenerate damaged muscle tissue. This process manifests differently in males and females, particularly in the satellite cell (SC) response, with sex hormones proposed to be the underlying factor mediating this difference. In Study 1, we demonstrated that 17β-estradiol (E2) elicited protective and pro-myogenic effects in response to electrical pulse stimulation (EPS), but that progesterone may antagonize this effect, leading to a net lack of influence in phases of the menstrual cycle (MC). In Study 2, we observed differing responses to EPS in oral contraceptive (OC) formulations that were based on the generation of OC, concomitant with the upregulation of estrogen and progesterone receptors (ERs and PRs). Interestingly, in humans, we observed a difference in the EIMD response, such that males had a higher SC response to damaging exercise and that females did not observe any changes in SC content but exhibited greater severe ultrastructural damage. These responses were weakly correlated to circulating concentrations of E2, suggesting that E2 may partially influence the EIMD response. Moreover, in Study 4, we found minimal differences in the EIMD response in naturally cycling (NC) females in the luteal phase versus OC users. Together, these data suggest that EIMD is influenced by numerous factors, with sex hormones potentially influencing damage and repair. Research in the field of physiology should continue to push for female inclusion, with particular emphasis on understanding the underlying mechanisms behind sex-based differences in the response to damaging stimuli and the role of sex hormones in this process.
Muscle Damage and Repair
Keywords: muscle damage; exercise; menstrual cycle; hormonal contraceptive; sex differences